ANALYSIS OF AMBITIOUS CHARACTERIZATION OF THE EVIL QUEEN THROUGH PLOT DEVELOPMENT “SNOW WHITE AND THE SEVEN DWARFS” MOVIE - Putu Sri Suci Ningsih (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2023)
This study presents how prose fiction can be reflected in human life through a feminist literary criticism approach one of them is to identify the ambitious characterization of the Evil Queen in the novel and film adaptation entitled Snow White and the Seven Dwarfs through plot development is closely related to human life. Human characterization certainly has an ambition that they will do anything to get what they want. This study has the purpose that to find out the ambitious characterization of the feminist side of the Evil Queen through plot development between the novel and film adaptation of Snow White and the Seven Dwarfs. This study used close reading as the method by reading the novel and watching the film adaptation of “Snow White and The Seven Dwarfs”. The result of this study is the Evil Queen has an ambitious characterization that is closely related to the feminist side both in the novel and film adaptation of Snow White and the Seven Dwarfs. Keywords: Prose fiction, Ambitious characterization, Plot development, Novel, Film Adaptation.